Desired weight loss and its association with health, health behaviors and perceptions in an adult population with weight excess: One-year follow-up - Cristina Bouzas; Cristina Bouzas; Cristina Bouzas; Maria del Mar Bibiloni; Maria del Mar Bibiloni; Maria del Mar Bibiloni; Silvia Garcia; Silvia Garcia; Silvia Garcia; David Mateos; David Mateos; David Mateos; et al. (Frontiers in Nutrition, 2022)
BackgroundMetabolic syndrome (MetS) worsens quality of life and increases mortality. Dissatisfaction with weight in patients with MetS may modify the effect of lifestyle interventions to achieve changes in health-related behaviors.ObjectiveTo assess 1-year changes in cardiovascular risk scores, self-perceived general health and health-related behaviors according to observed changes in desired weight loss during the first year of intervention in a large cardiovascular prevention trial.DesignProspective analysis of the PREDIMED-PLUS trial, including 5,499 adults (55–75 years old) with overweight or obesity at baseline.MethodsThe desired weight loss was the difference between ideal and measured weight. Tertiles of change in desired weight loss (1 year vs. baseline) were defined by the following cut-off points: ≥0.0 kg (T1, n = 1,638); 0.0 to −4.0 kg (T2, n = 1,903); ≤−4.0 kg (T3, n = 1,958). A food frequency questionnaire assessed diet and the Minnesota-REGICOR questionnaire assessed physical activity. The Framingham equation assessed cardiovascular risks. The changes in the severity of MetS were also assessed. The Beck Depression Inventory assessed depressive symptoms and the SF-36 assessed health-related quality of life. Data were analyzed using general linear models.ResultsBMI decreased at T2 and T3 (T1: 0.3, T2: −0.7, T3: −1.9). The most significant improvement in diet quality was observed at T3. Cardiovascular risk decreased at T2 and T3. Mean reductions in MetS severity score were: −0.02 at T1, −0.39 at T2 and −0.78 at T3. The perception of physical health increases in successive tertiles.ConclusionsIn older adults with MetS, more ambitious desired weight loss goals were associated with improvements in diet, cardiovascular health and perceived physical health during the first year of a healthy lifestyle intervention programme. Weight dissatisfaction needs to be considered by health professionals.Clinical trial registrationhttp://www.isrctn.com/ISRCTN89898870, identifier 89898870.